In-situ impregnation wood flame retardant treatment method
The in-situ impregnation method is used to generate phytate metal salt flame retardant inside the wood. Combined with the auxiliary effect of starch, the problem of smoke release of traditional wood flame retardant is solved, and the efficient flame retardant and smoke suppression effect is achieved, and the operation is simplified. Significantly improves the fire resistance and service life of the wood.
Patent Information
- Application Number
- CN202410134318.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-31
- Publication Date
- 2024-12-20
AI Technical Summary
Existing wood flame retardants release a large amount of smoke during combustion, increasing the risk of fire. The traditional method is complex to operate, making it difficult to achieve efficient flame retardant and smoke suppression effects.
In situ impregnation method is adopted to combine metal ions with aqueous carbon source solution and ammonium phytate to form a phytate metal salt flame retardant. Starch is used as an auxiliary flame retardant, and the flame retardant is made by vacuum negative pressure immersion and drying. Generated in situ inside the wood, a stable expanded carbon layer is formed to improve combustion stability and smoke suppression properties.
It significantly improves the flame retardant effect and smoke suppression performance of wood, reduces fire risk, extends the service life of wood, simplifies the treatment process, and improves the feasibility of operation.
Smart Images

Figure CN119159655A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of wood modification, and in particular relates to an in-situ impregnation method for wood flame retardant treatment. Background Art
[0002] The advantages of wood flame retardant treatment are as follows: 1) Improve fire resistance: Wood flame retardant treatment can significantly improve the fire resistance of wood. Untreated wood is easy to burn at high temperatures and burns quickly. Once it catches fire, the fire is easy to spread. The burning speed of wood treated with flame retardant is significantly slowed down, and it can withstand high temperatures for a long time, effectively delaying the spread of fire and buying more time for fire extinguishing. 2) Reduce fire risk: Wood flame retardant treatment can greatly reduce the possibility of fire. Since flame retardants can inhibit the burning speed of wood, the probability of fire is reduced. The wide application of wood treated with flame retardant in the fields of construction, furniture, packaging, etc. can greatly reduce the risk of fire and protect people's lives and property. Since flame retardant treatment can significantly improve the fire resistance of wood, it can reduce fire losses when a fire occurs. Wood treated with flame retardant is not easy to burn, can withstand high temperatures for a long time, effectively delay the spread of fire, and reduce the degree of damage to the surrounding environment caused by fire. This can not only reduce direct property losses, but also reduce indirect losses such as environmental pollution caused by fire. 3) Extend service life: Wood flame retardant treatment can extend the service life of wood. Untreated wood is susceptible to insect infestation, decay and other problems, and has a short service life. However, wood that has been treated with flame retardant can effectively resist these destructive factors, thereby extending the service life of the wood. This not only helps save resources, but also reduces maintenance costs.
[0003] In the prior art, wood flame retardant treatment mainly changes the thermal degradation pathway of wood by using flame retardants, reduces the total heat release and total smoke release of wood during combustion, and thus reduces its fire hazard. However, the mainstream flame retardants are mainly nitrogen-phosphorus, silicon-phosphorus, boron-phosphorus, etc. Among them, nitrogen-phosphorus is the most widely used because of its low price and excellent flame retardant effect. However, wood treated with nitrogen-phosphorus flame retardants often releases a lot of smoke during combustion, which greatly increases the fire hazard. Summary of the invention
[0004] The purpose of the present invention is to overcome the above problems existing in the prior art and provide a method for in-situ impregnation of wood for flame retardant treatment.
[0005] In order to achieve the above technical objectives and the above technical effects, the present invention is implemented through the following technical solutions:
[0006] An in-situ impregnation method for flame retardant treatment of wood comprises the following steps:
[0007] S1. Preparation of aqueous carbon source solution:
[0008] Starch and distilled water are mixed in a mass ratio of 1:5 to 1:20, and then a hydrogen peroxide solution is added in a mass ratio of starch to 30% H2O2 of 1:1 to 1:10, and after mixing, the mixture is heated at 70 to 100° C. for 3 to 6 hours, and the obtained aqueous transparent liquid is filtered to remove insoluble impurities to obtain an aqueous carbon source solution, which is divided into multiple portions for standby use;
[0009] S2. Preparation of phytic acid-based NP flame retardant:
[0010] Phytic acid and urea are mixed in a molar ratio of 1:6 to 1:20, and after mixing, they are heated at 90 to 120° C. for 5 hours to obtain an oily yellow liquid, and then freeze-dried at -50 to -80° C. for 12 to 24 hours using a freeze dryer to obtain white solid ammonium phytate;
[0011] S3. Preparation of metal salt solution:
[0012] Dissolving a metal sulfate in the aqueous carbon source solution obtained in step S1 to prepare a 0.1-0.8 mol / L metal salt solution;
[0013] S4. Preparation of flame retardant solution:
[0014] The white solid ammonium phytate obtained in step S2 is dissolved in the aqueous carbon source obtained in step S1 to prepare a 5-30 wt% flame retardant solution;
[0015] S5. Preparation of flame retardant modified wood:
[0016] The wood is placed in the metal salt solution obtained in step S3, and is subjected to a first vacuum negative pressure impregnation. The impregnated wood is dried and its moisture content is detected. When the moisture content is 20% to 50%, a flame retardant modified wood semi-finished product I is obtained. The flame retardant modified wood semi-finished product I is placed in the flame retardant solution obtained in step S4, and is subjected to a second vacuum negative pressure impregnation to obtain a flame retardant modified wood semi-finished product II. The flame retardant modified wood semi-finished product II is dried to obtain a flame retardant modified wood finished product.
[0017] Furthermore, in step S1, the starch is one of bean starch, potato starch, red cereal starch, wheat starch, water chestnut starch, lotus root starch, and corn starch.
[0018] Furthermore, in step S1, starch, 30% H2O2 and distilled water are mixed in a mass ratio of 1:2:7, and after mixing, they are heated at 70-90°C for 5-6 hours.
[0019] Furthermore, in step S2, phytic acid and urea are mixed in a molar ratio of 1:6 to 1:10, and after mixing, they are heated at 100 to 120° C. for 4 to 5 hours to obtain an oily yellow liquid, and then freeze-dried at -70 to -80° C. for 12 to 24 hours using a freeze dryer to obtain white solid ammonium phytate.
[0020] Furthermore, in step S3, the metal sulfate is at least one of copper sulfate, aluminum sulfate, iron sulfate, titanyl sulfate, nickel sulfate hexahydrate, and magnesium sulfate.
[0021] Furthermore, in step S3, a metal sulfate is dissolved in the aqueous carbon source solution obtained in step S1 to prepare a 0.3-0.6 mol / L metal salt solution.
[0022] Furthermore, in step S4, the white solid ammonium phytate obtained in step S2 is dissolved in the aqueous carbon source obtained in step S1 to prepare a 10-15 wt% flame retardant solution.
[0023] Furthermore, in step S5, the wood is poplar, radiata pine, fir, eucalyptus, birch, oak or basswood, and all the wood needs to be completely immersed in the soaking liquid.
[0024] Further, in step S5, the specific operations of the first vacuum negative pressure impregnation and the second vacuum negative pressure impregnation are: when the pressure reaches -0.01 to -0.09 MPa, observe whether there are bubbles coming out of the wood. If not, continue to maintain the pressure at -0.01 to -0.09 MPa for 1 to 5 hours; if so, continue to vacuum until no bubbles come out, and continue to maintain the pressure at this pressure for 1 to 5 hours.
[0025] Furthermore, in step S5, the specific operation of drying is: drying in a blast drying oven at a temperature of 101 to 105° C. for 6 to 8 hours.
[0026] The beneficial effects of the present invention are:
[0027] 1. The modified wood prepared by the present invention has excellent flame retardant effect and smoke suppression performance. The phytic acid metal salt precipitation can effectively adhere to the inside of the modified wood, enhance the stability of the residual carbon after combustion, improve the integrity of the wood after combustion, and reduce the fire hazard.
[0028] 2. The flame retardant modification treatment method for wood provided by the present invention is scientifically and reasonably designed, the overall operation of the method is simple, and the feasibility is strong. It has important value for wood utilization and processing and the diversification of wood materials.
[0029] Of course, any product implementing the present invention does not necessarily need to achieve all of the above advantages at the same time. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.
[0031] Figure 1 This is a scanning electron microscope image of the combustion char surface of the modified wood composite material;
[0032] Figure 2 This is a scanning electron microscope image of the modified wood composite material;
[0033] Figure 3 Cone calorimetry curves for modified wood composites;
[0034] Figure 4 This is a photo of the carbon residue after the cone calorimetry test of the modified wood composite material;
[0035] Figure 5 TG and DTG curves of residual carbon after cone calorimetry test of modified wood composites;
[0036] Figure 6 Schematic diagram of the preparation process of aqueous carbon source solution;
[0037] Figure 7 Schematic diagram of the preparation process of modified wood composites. DETAILED DESCRIPTION
[0038] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0039] Ammonium phytate is a commonly used flame retardant with good flame retardant properties and environmental friendliness. The phosphate and expanded carbon layer produced by the decomposition of ammonium phytate at high temperature have the characteristics of heat absorption and heat insulation, which can effectively slow down the burning rate of wood. Metal ions as auxiliary flame retardants can play a role in hydration effect, thermal stability, catalytic effect and heat load dispersion effect, thereby improving the flame retardant properties of the material and reducing the smoke release of the material. Starch as an auxiliary flame retardant can form a thicker and more stable expanded carbon layer on the surface of wood through dehydration and carbonization, enhance the heat absorption and heat insulation of the flame retardant expanded carbon layer, and improve the flame retardancy and smoke suppression of the material. In order to reduce the problem of large smoke release of nitrogen-phosphorus flame retardants, the present invention uses starch to prepare an aqueous carbon source solution, and the ammonium phytate flame retardant and metal ions are combined to modify the wood. The present invention is a material flame retardant integrated modification technology.
[0040] Select poplar as the test wood in each of the following embodiments, the poplar species is Jianghuai No. 1 poplar, selected from the Taihe County Forest Farm Experimental Base in Anhui Province, the Taihe County Forest Farm Experimental Base in Anhui Province (35 ° 10 '~ 35 ° 21 'N, 113 ° 40 '~ 113 ° 26 'E) belongs to the temperate monsoon climate, with sufficient sunshine, cold winter and hot summer, warm spring and cool autumn, distinct four seasons, average annual temperature of 12.8~14.8 ℃, average annual precipitation of 600~700 mm, and frost-free period of 200 days. The age of the poplar is selected to be 7 years, the tree height is 24 meters, and the diameter at breast height is 30.5 centimeters. The sample with a size of 20 mm (radial) × 120 mm (chord) × 150 mm (vertical) is cut from the sapwood part above the breast height of the poplar and is naturally dried, and the equilibrium moisture content of the dried poplar sample is 8-12%.
[0041] Example 1
[0042] This embodiment provides a method for in-situ impregnation of wood flame retardant treatment, comprising the following steps:
[0043] 1) Phytic acid and urea are heated at 120° C. for 5 h in a molar ratio of 1:6. First, 50% phytic acid is added to a three-necked flask and the temperature is kept at 90° C. for 30 min. Urea is then added and the mixture is heated at 120° C. for 5 h to obtain a yellow oily liquid. The liquid is placed in a -80° C. refrigerator and frozen for 24 h. After the liquid is completely frozen, it is freeze-dried at -80° C. for 24 h using a freeze dryer to obtain white solid ammonium phytate.
[0044] 2) Potato starch, 30% H2O2 and distilled water were mixed in a ratio of 1:2:7, and heated at 90°C for 6 hours to obtain a colorless transparent liquid, which was vacuum filtered three times to remove insoluble impurities to obtain an aqueous carbon source solution, which was divided into multiple portions for later use.
[0045] 3) dissolving the ammonium phytate obtained in step 1) in the aqueous carbon source solution to obtain a 15 wt% flame retardant solution. Then, dissolving a metal sulfate in the aqueous carbon source solution to obtain a 0.5 mol / L metal salt solution, wherein the metal sulfate is copper sulfate.
[0046] 4) The air-dried poplar wood sample is placed in a blast drying oven and dried at 103°C for 8 hours. The dried wood is placed in a metal salt solution and impregnated with a vacuum drying oven under negative pressure. When the pressure reaches -0.05MPa, observe whether the wood has bubbles. If so, continue to evacuate until no bubbles emerge, and maintain the pressure for 2 hours. The impregnated wood is dried and its moisture content is detected. When the moisture content is 30%, the flame-retardant modified wood semi-finished product I is obtained. The flame-retardant modified wood semi-finished product I is placed in the flame retardant solution obtained in step S4. When the pressure reaches -0.05MPa, observe whether the wood has bubbles. If so, continue to evacuate until no bubbles emerge, and maintain the pressure for 2 hours to obtain the flame-retardant modified wood semi-finished product II.
[0047] 5) placing the flame retardant modified wood semi-finished product II in a forced air drying oven, drying it at 60° C. for 8 hours, and then drying it at 103° C. for 8 hours to obtain a flame retardant modified wood finished product, i.e., a modified wood composite material.
[0048] 6) Referring to the national standard GB-T2406.2-2009 "Determination of Combustion Behavior of Plastics by Oxygen Index Method", the modified wood composite material is further sawn into oxygen index specimens of 3 mm (radial) × 6 mm (chordal) × 100 mm (longitudinal), and the limiting oxygen index value LOI of the specimen is tested and recorded; referring to GB8627-2007 "Test method for smoke density of burning or decomposition of building materials", the modified wood composite material is further sawn into smoke density specimens of 6 mm (radial) × 25 mm (chordal) × 25 mm (longitudinal), and the smoke density grade SDR of the specimen is tested and recorded; referring to ISO 5660-1 (1993) "Test method for heat release rate of building materials", the modified wood composite material is further sawn into conical calorimetric specimens of 20 mm (radial) × 100 mm (chordal) × 100 mm (longitudinal), and the radiant power of the specimen is tested and recorded. 2 Heat release and smoke release performance under test conditions.
[0049] Example 2
[0050] This embodiment is substantially the same as Embodiment 1, except that the metal sulfate is aluminum sulfate.
[0051] Example 3
[0052] This embodiment is substantially the same as Embodiment 1, except that the metal sulfate is ferric sulfate.
[0053] Example 4
[0054] This embodiment is substantially the same as Embodiment 1, except that the metal sulfate is titanyl sulfate.
[0055] Example 5
[0056] This embodiment is substantially the same as Embodiment 1, except that the metal sulfate is nickel sulfate hexahydrate.
[0057] Example 6
[0058] This embodiment is substantially the same as Embodiment 1, except that the metal sulfate is magnesium sulfate.
[0059] Comparative Example 1
[0060] This comparative example is basically the same as Example 1, except that the solutions used in the first and second immersion treatments of the wood are replaced by distilled water.
[0061] The relevant performance tests are as follows:
[0062] 1. Wood drug loading rate
[0063] Seven pieces of wood were taken as test pieces, with the size of 20 mm (radial) × 120 mm (chordal) × 150 mm (longitudinal); based on the mass difference of the six pieces of wood before and after treatment with Examples 1 to 6 and Comparative Example 1, the drug loading rate (WPG, %) of the modified wood was calculated:
[0064]
[0065] Wherein, M0 is the absolute dry weight of the wood before modification, and M1 is the absolute dry weight of the wood after modification.
[0066] The drug loading rates of wood in Examples 1 to 6 are shown in Table 1:
[0067] Table 1
[0068]
[0069]
[0070] In the first impregnation under negative pressure, the metal ion solution can enter the wood, and the metal ions are evenly distributed in the wood pores under the adsorption of the starch carbon source; in the second impregnation under negative pressure, the ammonium phytate reacts with the metal ions inside the wood to form a phytate metal salt flame retardant. During the impregnation process, the starch carbon source controls the reaction rate of anions and cations by adjusting the viscosity of the solution, preventing the phytate metal salt complex from accumulating on the wood surface and hindering the entry of the ammonium phytate into the wood.
[0071] The drug loading rates of Examples 1 to 6 are between 16.9% and 19.1%, which proves that the wood flame retardant method of the invention can generate the flame retardant in situ inside the wood, and the flame retardant treatment process is simple and has good effects.
[0072] 2. SEM-EDS analysis of modified wood composites
[0073] Figure 2 The microscopic morphology of the surface of different modified wood composite materials. The phytic acid metal ion complex is distributed on the surface of the pipes and pores in the wood. The EDX spectrum shows that the metal ions are evenly distributed in the vessels and pits of the wood. Phytic acid metal salts have high thermal stability and can serve as a heat-absorbing and heat-insulating physical barrier during the combustion of modified wood composite materials to prevent the internal materials from violently pyrolyzing and releasing heat. Metal phytates decompose in the early stage / initial stage of the combustion of modified wood composite materials. The decomposition of metal phytates is an endothermic reaction and produces non-combustible gases to dilute oxygen and combustible gases. During the combustion of modified wood composite materials, the metal oxides generated by the oxidation reaction of phytic acid metal salts have a large specific surface area. Starch increases the thickness and thermal stability of the expanded carbon layer of the flame retardant through dehydration and carbonization, adsorbs smoke, and is evenly covered on the surface of the wood, which can simultaneously reduce the release of heat and smoke during wood combustion.
[0074] 3. Oxygen Index and Smoke Density of Modified Wood Composites
[0075] The limiting oxygen index (LOI) and smoke density tests were carried out on the modified wood composites to study the fire safety of the modified wood composites after treatment, as shown in Table 2:
[0076] Table 2
[0077]
[0078]
[0079] Table 2 shows the effect of phytic acid metal salts on the LOI value and smoke density rating (SDR) of poplar wood. It can be seen that the LOI value of poplar wood in Control Example 1 is only 18.9%, and it is easy to ignite under normal atmospheric conditions (oxygen content is about 21%). Therefore, the untreated poplar wood in Control Example 1 is a flammable material. After being ignited, the untreated poplar wood burns more fully, mainly with flames, releases a large amount of heat during the combustion process, has less smoke products, and has a lower smoke density.
[0080] The LOI of poplar wood in Examples 1 to 6 is between 35.9% and 41.2%, indicating that the modified wood composite material is difficult to ignite in the air, and its flame retardant properties are significantly improved. The LOI of Example 1 is 41.2%, which is 118.0% higher than that of Control Example 1, which is mainly attributed to the flame retardant effect of phytic acid metal salts. After flame retardant treatment, the smoke density level of the material usually increases to a certain extent. The smoke density of the untreated poplar wood in Control Example 1 is low at only 7.72 due to complete combustion. The smoke density levels (SDR) of Examples 1 to 6 are all increased compared to Control Example 1, but all meet the requirements of smoke density level (SDR) ≤ 75 in GB / T8627-2007 "Test Method for Smoke Density of Combustion or Decomposition of Building Materials". The flame retardant component hinders the combustion of wood, and the incomplete combustion reaction of the material generates more smoke, resulting in an increase in smoke density. The copper phytate metal salt in Example 1 can form a porous copper-containing oxide, which can effectively adsorb the smoke products during the combustion of the material. The smoke density rating (SDR) of the composite material is only 8.38, which is very close to that of unflame-retardant poplar wood, indicating that the introduction of the Cu element has a significant effect on improving the smoke suppression performance of the modified wood composite material.
[0081] 4. Cone calorimetry analysis of modified wood composites
[0082] Total heat release (THR) and heat release rate (HRR) analysis, Figure 3 Figure 3 is the heat release rate HRR (a), total heat release THR (b), smoke release rate SPR (c) and total smoke release TSP (d) curves of the modified wood composite material. Table 4 is the heat release parameters of the combustion of the modified wood composite material. Figure 3 a is the heat release rate of wood combustion. The HRR of control example 1 rises rapidly from 0 to 60 seconds and reaches the first heat release peak (217.05KW / m 2 ), the wood burns quickly and releases heat under high temperature radiation; at this time, the surface wood is carbonized by heat to form a char layer, which can play a certain role in heat insulation and oxygen isolation, so the HRR curve is relatively stable before 450s. As the burning time increases, the char layer on the surface of the wood is burned or cracked, and a large amount of oxygen enters the surface and interior of the wood, intensifying the combustion of the internal wood, and reaching the second heat release peak around 600s (371.89KW / m 2 ).
[0083] Compared with the untreated material in Control Example 1, the modified wood composite materials in Examples 1 to 6 reach the first heat release peak earlier and the peak value of the first heat release peak is lower. The peak value of the first heat release peak of the treatment group in Example 1 (154.16 KW / m 2) is only 71.02% of the wood in Control Example 1, and the time is advanced by 30s. In the present invention, the phytic acid metal salt in the wood flame retardant contains P element, which catalyzes the dehydration of the wood and the starch carbon source in the flame retardant to form carbon. The coke layer generated in this stage is more stable and dense, and the barrier effect on oxygen and heat penetration and the release of combustible gas inside the material is enhanced. Therefore, Example 1 reaches the second heat release peak at around 700s, which is 80s later than the untreated material. The second heat release peak is only 101.01KW / m 2 , which is 72.83% lower than untreated materials, which greatly reduces the fire hazard.
[0084] The heat release properties of the modified wood composites are shown in Table 3:
[0085] Table 3
[0086] Group Comparative Example 1 Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 PHRR1 217.05 154.16 239.39 229.64 234.15 240.12 223.32 TPHRR1 54 32 38 34 35 42 33 PHRR2 371.89 101.01 143.51 181.05 197.83 154.45 202.55 TPHRR2 627 706 582 572 558 729 589 THR 134.34 87.93 108.04 111.18 114.44 112.3 111.68 Mean-HRR 111.95 73.27 89.94 92.51 95.36 93.55 93.06
[0087] Note: PHRR1 is the first heat release peak, KW / m 2 ; TPHRR1 is the time corresponding to the first heat release peak, s; PHRR2 is the second heat release peak, KW / m 2 ; TPHRR2 is the time to reach the second heat release peak, t; THR is the total heat release, MJ / m 2 ; Mean-HRR is the average heat release rate, KW / m 2 .
[0088] Table 3 shows the average heat release rate of the materials in Examples 1 to 6, where the mean-HRR of Example 1 is 73.27 KW / m 2 , which is 34.55% lower than the untreated material in Control Example 1. Figure 3 b It can be seen that the total heat release of Examples 1 to 6 is lower than that of Control Example 1, among which Example 1 has the best effect, and its THR is 87.93, which is 34.54% lower than that of Control Example 1.
[0089] Total heat release THR of modified wood composite materials within 1200s, in MJ / m 2 As shown in Table 4:
[0090] Table 4
[0091] Time(s) Comparative Example 1 Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 60 6.46 6.04 8.3 8.69 8.18 8.04 8.15 120 17.12 12.43 17.53 17.76 18.11 18.03 16.53 180 25.14 18.07 25.35 24.73 26.19 26.03 23.66 240 32.77 23.28 32.54 31.04 33.62 32.94 30.51 300 40.42 28.35 39.57 37.39 40.94 39.15 37.28 360 48.03 33.4 46.4 43.89 48.32 45.07 44.16 600 87.65 54.48 76.16 78.95 86.03 68.7 84.27 900 121.46 77.52 97.68 99.92 103.34 102.74 100.04 1200 134.34 87.93 108.04 111.18 114.44 112.3 111.68
[0092] Table 4 shows the total heat release THR of the materials corresponding to different burning times. It can be seen that the heat release of the wood in Examples 1 to 6 within 600s is lower than that in Control Example 1, and the fire hazard is greatly reduced, which is consistent with the heat release rate result. The heat release of the modified wood composite material in Example 1 at each stage is lower than that in Control Example 1. This is because the metal ions promote the carbon source in the flame retardant to quickly form a heat-insulating and oxygen-insulating layer on the surface of the wood during the combustion process, and the generated acidic substances further catalyze the carbonization of the internal wood, thereby reducing the heat release of the modified wood composite material.
[0093] Wood will release smoke and toxic gases during the combustion process, and the smoke suppression effect is also the key to evaluating the flame retardant properties of materials. Figure 3 The smoke release rate (SPR) of the modified wood composite material in c, Example 1 approaches 0 after 200s, indicating that the smoke suppression effect is excellent. Figure 3 d, the total smoke generation of the modified wood composite material decreased significantly, among which Example 1 had the best smoke suppression effect, compared with 2.36m 2 Down to 0.4m 2 This is because phytic acid metal salts accumulate in large quantities in the wood ducts, increasing the specific surface area of the wood and having an excellent absorption effect on smoke.
[0094] Figure 4 This is a photo of the residual carbon after the cone calorimetry test of the modified wood composite material. The control example 1 has less residual after combustion, mostly in the form of white ash. The materials in Examples 1 to 6 are in blocks after combustion, and the integrity of the carbon layer is good. Among them, there is ash on the surface of Example 6, Example 2, and Example 5 as a whole, and the lower layer is a carbon layer. There is a small amount of ash on the surface of Example 3, and the rest is covered with black and red substances (ferroferric oxide). The presence of a large amount of ferroferric oxide enhances the integrity of the carbon layer and improves the adsorption performance of flue gas. The surface of Example 4 is attached with yellow substances (titanium hydroxide), and the overall structure is complete, but there are many cracks. The surface of Example 1 is all attached with red substances (cuprous oxide), and the overall structure is complete, the carbon layer is intact, and the degree of cracking is low. The PAN-Cu flame retardant in Example 1 promotes the charring of wood and increases the charring rate of wood. At the same time, the cuprous oxide generated during the combustion process enhances the stability of the carbon layer.
[0095] 5. Analysis of flame retardant and smoke suppression mechanism of modified wood composite materials
[0096] 1. Mechanism of flame retardant treatment process:
[0097] Ammonium phytate has abundant phosphate and ammonium groups, which can form coordination bonds with metal ions to form complex precipitation inside the wood. Hydrolyzed starch can adjust the viscosity of ammonium phytate solution and metal ion solution, slow down the reaction rate of ammonium phytate and metal ions, and enable ammonium phytate to enter the wood and generate ammonium phytate metal salt complex in situ. Hydrolyzed starch can also act as a binder, forming a strong bond with wood fibers, helping the ammonium phytate metal salt complex formed by ammonium phytate and metal ions to be more evenly fixed inside the wood, thereby improving the overall flame retardant effect of the wood.
[0098] 2. Mechanism of combustion process:
[0099] At high temperatures, phytic acid metal salt complexes decompose to produce phosphoric acid or other phosphorus-containing compounds, and form an oxygen-isolating and heat-insulating protective layer on the wood surface, slowing down the burning rate of the wood; starch as a carbon source is conducive to the formation of an expanded carbon layer and enhancing the thickness and thermal stability of the carbon layer.
[0100] The expanded carbon layer has excellent oxygen and heat insulation effects, which prevents the wood from contacting with oxygen and external heat sources, and limits the spread of flames. At the same time, the expanded carbon layer slows down the rate of temperature rise inside the wood, prolonging the structural integrity of the wood in the event of a fire. In addition, the complex migrates to the surface along with the expanded carbon layer to enhance the thermal stability of the expanded carbon layer, further reducing the risk of fire spread. The carbon layer plays a certain protective role on the interior of the wood, slowing down the temperature rise inside the wood and maintaining a certain structural strength of the wood.
[0101] 3. Modification mechanism of improving thermal stability of wood char
[0102] Figure 5 The TG and DTG curves of wood char obtained after cone calorimetry test. Figure 5 a It can be seen that the thermal stability of the untreated carbon residue in the control example 1 is poor, and it decomposes rapidly after 400℃, indicating that it cannot protect the internal materials well under the high temperature of the combustion process. Figure 5 b It can be seen that there are two main decomposition processes of the charcoal residue of the modified wood composite material, and the phytic acid metal salt effectively increases the main decomposition temperature of the wood charcoal residue.
[0103] The TG analysis of the wood char in Examples 1 to 6 shows the dual carbonization mechanism of phytic acid metal salts, that is, in addition to promoting the endothermic dehydration of wood, catalytic carbonization, and adsorption of flue gas during wood combustion, phytic acid metal salts also further enhance the thermal stability of the solid charcoal product of wood combustion.
[0104] The residual mass of the charcoal residue of the modified wood composite material in Example 3 after the TG test is 87.41%, which is 154% higher than that in Control Example 1. This is mainly attributed to the good thermal stability of the metal oxides and the catalytic aromatization / graphitization of the metal substances through the "formation-decomposition of carbide intermediates" mechanism to form a large aromatic planar structure of the wood, thereby promoting the thermal degradation of the wood at high temperature to form a solid carbon with a high degree of graphitization and high thermal stability.
[0105] According to the above analysis, the flame retardant and smoke suppression mechanism of phytic acid metal salts can be summarized as follows: during the combustion of modified wood composite materials, metal phytates first decompose to produce a large amount of phosphoric acid / polyphosphates, metal phosphates and metal oxides, and produce non-combustible gases to dilute oxygen and combustible gases. The dehydration and carbonization of starch prompts the flame retardant to form a thicker and more thermally stable expanded carbon layer on the wood surface. Due to the dual carbonization effect of phosphoric acid substances and metal ions, the combustion of wood is directed to generate more residual carbon and less heat release and smoke release. In addition, due to the large amount of deposition of phytic acid metal salts inside the wood, the entry of heat and oxygen is effectively isolated, and it has a certain adsorption effect on smoke. Finally, due to the redox occurrence of metal oxides during the combustion process, this will catalyze the formation of highly graphitized residual carbon, enhance the stability of the residual carbon, which will further reduce heat release and smoke release.
[0106] The preferred embodiments of the present invention disclosed above are only useful to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A method for in-situ impregnation of wood flame retardant treatment, characterized in that: The steps include: S1. Preparation of aqueous carbon source solution: Starch and distilled water are mixed in a mass ratio of 1:5 to 1:20, and then a hydrogen peroxide solution is added in a mass ratio of starch to 30% H2O2 of 1:1 to 1:10, and after mixing, the mixture is heated at 70 to 100° C. for 3 to 6 hours, and the obtained aqueous transparent liquid is filtered to remove insoluble impurities to obtain an aqueous carbon source solution, which is divided into multiple portions for standby use; S2. Preparation of phytic acid-based NP flame retardant: Phytic acid and urea are mixed in a molar ratio of 1:6 to 1:20, and after mixing, they are heated at 90 to 120° C. for 5 hours to obtain an oily yellow liquid, and then freeze-dried at -50 to -80° C. for 12 to 24 hours using a freeze dryer to obtain white solid ammonium phytate; S3. Preparation of metal salt solution: Dissolving a metal sulfate in the aqueous carbon source solution obtained in step S1 to prepare a 0.1-0.8 mol / L metal salt solution; S4. Preparation of flame retardant solution: The white solid ammonium phytate obtained in step S2 is dissolved in the aqueous carbon source obtained in step S1 to prepare a 5-30 wt% flame retardant solution; S5. Preparation of flame retardant modified wood: The wood is placed in the metal salt solution obtained in step S3, and is subjected to a first vacuum negative pressure impregnation. The impregnated wood is dried and its moisture content is detected. When the moisture content is 20% to 50%, a flame retardant modified wood semi-finished product I is obtained. The flame retardant modified wood semi-finished product I is placed in the flame retardant solution obtained in step S4, and is subjected to a second vacuum negative pressure impregnation to obtain a flame retardant modified wood semi-finished product II. The flame retardant modified wood semi-finished product II is dried to obtain a flame retardant modified wood finished product.
2. The in-situ impregnation method for wood flame retardant treatment according to claim 1, characterized in that: In step S1, the starch is one of bean starch, potato starch, red cereal starch, wheat starch, water chestnut starch, lotus root starch, and corn starch.
3. The in-situ impregnation method for wood flame retardant treatment according to claim 1, characterized in that: In step S1, starch, 30% H2O2 and distilled water are mixed in a mass ratio of 1:2:7, and after mixing, they are heated at 70-90°C for 5-6 hours.
4. The in-situ impregnation method for fire retardant treatment of wood according to claim 3, characterized in that: In step S2, phytic acid and urea are mixed in a molar ratio of 1:6 to 1:10, and after mixing, they are heated at 100 to 120° C. for 4 to 5 hours to obtain an oily yellow liquid, and then freeze-dried at -70 to -80° C. for 12 to 24 hours using a freeze dryer to obtain white solid ammonium phytate.
5. The in-situ impregnation method for fire retardant treatment of wood according to claim 1, characterized in that: In step S3, the metal sulfate is at least one of copper sulfate, aluminum sulfate, iron sulfate, titanyl sulfate, nickel sulfate hexahydrate, and magnesium sulfate.
6. The in-situ impregnation method for fire retardant treatment of wood according to claim 1, characterized in that: In step S3, a metal sulfate is dissolved in the aqueous carbon source solution obtained in step S1 to prepare a 0.3-0.6 mol / L metal salt solution.
7. The in-situ impregnation method for fire retardant treatment of wood according to claim 1, characterized in that: In step S4, the white solid ammonium phytate obtained in step S2 is dissolved in the aqueous carbon source obtained in step S1 to prepare a 10-15 wt% flame retardant solution.
8. The in-situ impregnation method for fire retardant treatment of wood according to claim 1, characterized in that: In step S5, the wood is poplar, radiata pine, fir, eucalyptus, birch, oak or basswood, and all the wood needs to be completely immersed in the soaking liquid.
9. The in-situ impregnation method for fire retardant treatment of wood according to claim 1, characterized in that: In step S5, the specific operations of the first vacuum negative pressure impregnation and the second vacuum negative pressure impregnation are: when the pressure reaches -0.01 to -0.09 MPa, observe whether there are bubbles coming out of the wood. If not, continue to maintain the pressure at -0.01 to -0.09 MPa for 1 to 5 hours; if so, continue to vacuum until no bubbles come out, and continue to maintain the pressure at this pressure for 1 to 5 hours.
10. The in-situ impregnation method for fire retardant treatment of wood according to claim 1, characterized in that: In step S5, the specific operation of drying is: drying in a blast drying oven at a temperature of 101 to 105° C. for 6 to 8 hours.
Citation Information
Cited By
Flame-retardant modified wood, preparation method and application
CN120245153A
High-temperature-resistant flame-retardant wood composite board and preparation method thereof
CN122560187A
